Characterization of Activated Coconut Shell Charcoal as a Zinc Absorbent for Used Oil Lubricant - Erawati, Emi; Haryanto, Haryanto; Astuti, Neysa Wirantika; Prasetyanti, Annida Mitha (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2020)
Lubricating oil is classified as B3 waste (hazardous and toxic waste). In the lubricating oil consists of zinc waste which is very dangeraous for healt and environment. So that to handle lubricating oil is used the adsorption method using coconut shell as adsorbent. This study aims to determine the efficiency of zinc adsorption on lubricating oil with stirring speed, percent solvent, mesh size, and mass of adsorbent variation; to learn the equibilium equation of adsorpsion of Zn metal ion on the activated carbon of coconut shell charcoal using Freundlich and Langmuir equilibirium; and to calculate adsorbtion kinetic constanta using the pseudo first model or pseudo second order kinetics approach. Coconut shells was heated at a temperature of 300C for 1 hour for the driving process . Furthermore, charcoal was soaked in 25% HCl for 18 hours. After being neutralized to pH 7, the charcoal was activated for 3 hours at a temperature of 500C and stored in a closed place. Coconut shell adsorbent and H2SO4 solvent were put into a beaker glass containing 400 ml of lubricating oil and stirred for 2 hours, every 30 minutes intervals were taken 50 ml to destruction for 2 hours with 68% HNO3. The zinc concentration before and after adsorption were measured using AAS. This study uses the Langmuir isotherm and Freundlich Isotherm models. The greatest efficiency of zinc adsorption with solvent percent variation 0.5% is 95.0567% and 99.9375% in adsorbent mass variation of 10 gram.